The influence of superelevated profiles of paving block structures on their load-bearing behavior. (15th June 2016) - Hengl, H.L.; Füssl, J.
Highlights: We developed a tool which is able to capture the effects of superelevated profiles. Two different predominating structural failure mechanisms could be identified. Parameter studies were performed to identify the influence of structural parameters. A sound evidence for the positive influence of superelevated profiles is provided. Abstract: Paving block pavements are an ecological, economical and space forming valuable type of road surface, and therefore, the demand is continuously increasing. Nevertheless, immature design concepts often lead to unexpected performance, which reduces confidence in these structures. For example, positive effects on the load-bearing behavior due to superelevation of the cross profiles are not considered within existing design concepts, even though their influence on the performance of a block pavement structure is, according to the experience of skilled engineers, very large. For this reason, this work focuses on the influence of superelevated cross profiles of paving block structures on their load-bearing behavior. A 3D finite element model has been developed, which is able to take the interaction behavior between paving blocks, in tangential as well as normal direction, accurately into account. Numerous parameter studies were performed to identify the influence of structural parameters, like the size of the superelevation, the number and dimension of paving blocks, the interaction between them, and the loading situation, on the structural behavior. From these simulations, two different predominating structural failure mechanisms could be identified: (i) snap through buckling, for very small superelevations of the cross profile and (ii) the formation of a kinematic chain, which is initiated very fast for high superelevations. At the transition from one to the other mechanism, the highest loading capacity of a paving block structure could be numerically observed. The corresponding superelevation, for a specific road width, changes interestingly only very low with changing boundary and interaction conditions. Therefore, based on comprehensive numerical calculations, it was possible to define an optimal region of superelevation-to-road-width ratios. Moreover, a huge influence of the cross profile on the load bearing capacity of block pavement structures could be detected mechanically sound for the first time. Consideration of these effects within the design process may strongly improve the performance prediction of paving block constructions.